Drivers of success of the renewable energy firms’ partnerships - Salavisa, I.; Sousa, C.; Calapez, T. (2º Workshop “Dinâmicas Socioeconómicas e Territoriais Contemporâneas”, 2016)
This paper focuses on the strategic partnerships established by firms operating in the renewable energy technologies sector in Portugal. The goal is to unveil the drivers of success of these partnerships, and their main characteristics. The partnerships are established between young firms which are developing new generation energy technologies within specific niches (Kemp et al, 1998; Bergek et al, 2008; Hekkert and Negro, 2009); between these firms and the ‘old’ incumbent companies, that is, across levels in a multi-level framework (Geels, 2002; Grin, Rotmans and Schot, 2011); and, finally, between these firms and a diversity of organisations such as universities and public laboratories, government agencies, venture capital companies, private equities, industry associations, civil society associations, etc., both national and international. In the case under study, the incumbents have adopted a proactive strategy to deal with the emergence of new generation renewables, as they have done in other countries (Stenzel and Franzel, 2008). This was due not only to the perception of an interesting and promising new business area, but also to the existence of very generous incentives provided by the government such as long term contracts with feed-in tariffs, privileged access to the grid, subsidies, etc. They have become important actors in building the renewables cluster in Portugal. In terms of the transition pathways diversity (Markard et al., 2012; Smith et al., 2005), this is described as a reconfiguration pathway (Geels and Shot, 2007; Verbong and Geels, 2010), where the old regime actors reorient their strategies, though keeping in place conventional energy production as well. The partnerships have been built and managed to access resources (e.g. knowledge, complementary assets, and financial resources). In this process, the firms establish each partnership’s goal, choose the most appropriate partners and the channels of interaction, develop trust and assess the results obtained. The research draws on primary data collected through detailed interviews with the founders or CEOs of 60 Portuguese renewable energy technologies firms, which encompass the vast majority of the firms operating in the sector in Portugal. These companies have identified and described a set of 174 strategic partnerships, which are the base of our empirical work. In a first step, we conducted an analysis aiming to characterize the strategic relationships of the firms regarding: - the partnership motivation; - the partners’ identification; - the partners’ characteristics: type (other firms, university, government, civil society associations) and location; - the type of interaction; - the degree of trust among the partners; - the degree of dependence between the partners. In a second step, we conducted an econometric analysis to identify the factors affecting the success of the partnerships. The dependent variable is the degree of the partnership goal achievement, assessed by the interviewed firms (in a Likert 7-point scale) and the independent variables reflect the firm’s choices as well as the main characteristics of the partnerships. The paper aims to further knowledge about the drivers of success of the partnerships deployed in the renewables sector. Hence, it assesses the contribution of elements such as the objectives, types of partners, degree of trust, forms of interaction, and other aspects to the reported success of the partnerships. We also attempt at drawing conclusions on the way these partnerships have contributed to building the renewables sector in Portugal.